Influence of chemical composition and cold deformation on aging precipitation behavior of high nitrogen austenitic stainless steels - Li, Hua-bing; Jiang, Zhou-hua; Feng, Hao; Zhu, Hong-chun; Zhang, Zu-rui (Journal of Central South University, 2013)
The influence of chemical composition and cold deformation on aging precipitation behavior of 18Cr-16Mn-2Mo-1.1N (HNS-A), 18Cr-16Mn-1.3N (HNS-B), 18Cr-18Mn-2Mo-0.96N (HNS-C) and 18Cr-18Mn-2Mo-0.77N (HNS-D) high nitrogen austenitic stainless steels was investigated. The results show that the “nose” temperatures and incubation periods of the initial time-temperature-precipitation (TTP) curves of aged HNSs are found to be 850 °C, 60 s; 850 °C, 45 s; 850 °C, 60 s and 900 °C, 90 s, respectively. Based on the analysis of SAD patterns, the coarse cellular Cr 2 N precipitate which presents a lamellar structure has a hexagonal structure of a =0.478 nm and c =0.444 nm. The χ phase corresponding to a composition of Fe 36 Cr 12 Mo 10 , is determined to be a body-centered cubic structure of a =0.892 nm. The precipitating sensitivity presents no more difference with the nitrogen content increasing from 0.77% to 0.96%, but exhibits so obviously that the cellular precipitates nearly overspread the whole field. The addition of Mo element can restrain the TTP curves moving left and down, which means decreasing the sensitivity of aging precipitation. With increasing the cold deformation, the sensitivity of precipitation increases obviously.